Meta-cinematic cultism: between high and low culture - Chinita, Fátima (2016)
ABSTRACT - Meta-cinema can depict film viewers’ attitudes towards cinema and their type of devotion for films. One subcategory of viewers - which I call meta-spectators - is highly specialized in its type of consumption, bordering on obsession. I contend that there are two main varieties of meta-cinematic reception, not altogether incompatible with one another, despite their apparent differences. As both of them are depicted on meta-cinematic products, the films themselves are the best evidence of my typology. My categories of film viewers are the ‘cinephile’, an elite prone to artistic militancy and the adoration of filmic masters; and the ‘fan’, a low culture consumer keen on certain filmic universes and their respective figures and motifs. I will base my rationale on four films that portray such reception practices: Travelling Avant (Jean-Charles Tacchella, 1987, FRA), The Dreamers (Bernardo Bertolucci, 2003, UK/FRA/ITA); Free Enterprise (Robert Mayer Burnett, 1998, USA); Fanboys (2009, Kyle Newman, USA).